Tillage effects on maize yield in a Colombian savanna oxisol : Soil organic matter and P fractions - Basamba, T.A.A.; Barrios, E.; Amézquita Collazos, Edgar; Rao, Idupulapati M.; Singh, B.R. (Elsevier, 2006)
Soil organic matter (SOM) and phosphorus (P) fractions play a key role in sustaining the productivity of acid-savanna oxisols and are greatly influenced by tillage practices. In 1993, a long-term experiment on sustainable crop rotation and ley farming systems was initiated on a Colombian acid-savanna oxisol to test the effects of grain legumes, green manures, intercrops and leys as possible components that could increase the stability of systems involving annual cereal crops. Five agropastoral treatments (maize monoculture MMO, maize soybean rotation MRT, maize soybean green manure rotation MGM, native savanna control NSC and maize-agropastoral rotation MAP) under two tillage systems (no till-NT and minimum tillage-MT) were investigated. The effects of NT and MT on SOM and P fractions as well as maize grain yield under the five agropastoral treatments were evaluated. Results showed that soil total C, N and P were generally better under no-till as compared to minimum-tilled soils. While P fractions were also generally higher under no-till treatments, SOM fractions did not show any specific trend. Seven years after establishment of the long-term ley farming experiment (5 years of conventional tillage followed by 2 years alternative tillage systems), MT resulted into moderately higher maize grain yields as compared to NT. The MGM rotation treatment had significantly higher values of maize yield under both tillage systems (4.2 Mg) compared to the NSC (2.3 Mg ha?1). Results from this study indicate that the rotational systems (maize soybean green manure and maize-pastures) improved the soil conditions to implement the no-till or minimum tillage systems on Colombian savanna oxisol.